الدور الدعوي والإجتماعي لجمعية الإرشاد والإصلاح في وادي سوف 1989 /2023 - بوغزالة محمد صفاء; مسعي محمد عواطف; حريز عبد القادر عقيلة (جامعة الوادي - University of Eloued, 2025)
"مرت الجزائر بعدة ظروف ساهمت في تأسيس العديد من الجمعيات, وما ساعد على ذلك الإنفتاح السياسي الذي عرفته الجزائر حيت انتقلت إلى التعددية الحزبية الذي سمح بتأسيس الجمعيات منها جمعية الإرشاد والإصلاح سنة 1989م, وكان لها عدة مكاتب ولائية منها المكتب الولائي بالوادي ومن أهم أهدافها العمل الخيري وأهم نشاطاتها فتح مكاتب بلدية وفروع .....إلخ. اهتمت الجمعية بالقرآن الكريم وأنشئت هيئة له بهدف التعليم والتحفيظ للفئات المختلفة خاصة الأطفال والنساء في إطار تربوي منظم وفتحت عدة مدارس وقامت بإنشاء روضات تعنى بتربية الأطفال وقد أدت المربيات دورا أساسيا في هذا المجال كما أولت الجمعية والديوان الوطني اهتمام كبير بمحو الأمية وحرصت على تنشيط الجانب الثقافي والإعلامي وهذا من خلال تنظيم محاضرات وندوات ومعارض. فيما يخص الجانب الاجتماعي اهتمت الجمعية بالعمل الخيري منها كفالة اليتيم ودعم الأسر المحتاجه والقيام بالأنشطة الخيرية ودعم الأسر المنتجة كذلك اهتمت بالإغاثة في فتره الأزمات محليا منها حملات التبرع وطنيا ومنها مساعدات إلى ولاية ايليزي وخارجيا تقديم مساعدات إلى العديد من الدول. وتعتبر هذه الجمعية من بين أهم الجمعيات التي أنشت في الجزائر كونها كانت عنصر فعال ولازالت إلى حد الآن فهي ليست فقط مهتمة بالجانب الدعوي والإجتماعي ولكن كان لها أثر الكبير في السياسات القائمة في الجزائر. "Algeria has experienced several circumstances that contributed to the establishment of numerous associations. This was facilitated by the political openness that Algeria experienced, as it transitioned to a multi-party system. This allowed for the establishment of associations, including the Guidance and Reform Association in 1989. It had several provincial offices, including the provincial office in El Oued. Its most important goals were charitable work, and its most important activities included opening municipal offices and branches, etc. The Society paid attention to the Holy Quran and established an authority for it with the aim of teaching and memorizing it to different groups, especially children and women, within an organized educational framework. It opened several schools and established Quranic kindergartens concerned with raising children. Teachers played a fundamental role in this field. The Society and the National Office also paid great attention to eradicating illiteracy and were keen to activate the cultural and media aspects through organizing lectures, seminars and exhibitions Regarding the social aspect, the association focused on charitable work, including sponsoring orphans, supporting needy families, carrying out charitable activities, and supporting productive families. It also focused on relief during times of crises locally, including donation campaigns nationally, including aid to Illizi State, and externally, providing aid to many countries. This association is considered one of the most important associations established in Algeria, as it was an active element and still is to this day. It is not only concerned with the advocacy and social aspects, but it also had a major impact on the policies existing in Algeria. "
مذكرة ماستر قسم التاريخ تخصص المغرب العربي المعاصر
Keywords: الدور الدعوي; الدورالإجتماعي; جمعية الإرشاد والإصلاح; وادي سوف; The role of advocacy; the social role; the Guidance and Reform Association; Wadi Souf